2016
DOI: 10.3389/fpls.2016.01706
|View full text |Cite
|
Sign up to set email alerts
|

Role of the GacS Sensor Kinase in the Regulation of Volatile Production by Plant Growth-Promoting Pseudomonas fluorescens SBW25

Abstract: In plant-associated Pseudomonas species, the production of several secondary metabolites and exoenzymes is regulated by the GacS/GacA two-component regulatory system (the Gac-system). Here, we investigated if a mutation in the GacS sensor kinase affects the production of volatile organic compounds (VOCs) in P. fluorescens SBW25 (Pf.SBW25) and how this impacts on VOCs-mediated growth promotion and induced systemic resistance of Arabidopsis and tobacco. A total of 205 VOCs were detected by Gas Chromatography Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…At the intracellular level, the role of the Gac system in the regulation of the 205 VOCs produced by P. fluorescens SBW25 was investigated. It appeared that the synthesis of 24 VOCs is regulated by the Gac system 104 . Eventually, all of these studies should shed light on the ecological role of VOCs.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…At the intracellular level, the role of the Gac system in the regulation of the 205 VOCs produced by P. fluorescens SBW25 was investigated. It appeared that the synthesis of 24 VOCs is regulated by the Gac system 104 . Eventually, all of these studies should shed light on the ecological role of VOCs.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…On the one hand, it is expected that the production of BVOCs is influenced by chemical-physical parameters, such as nutrient availability, temperature, pH, relative humidity, and the presence or absence of oxygen. On the other hand, recent studies have shown that the production of BVOCs can be stimulated or inhibited during the interaction of bacteria with their hosts consistently with a biological activity of BVOCs in the host [184][185][186][187]. Specifically, in several bacteria, BVOCs production is controlled by GacS/GacA two-component system which, in enteric bacteria and fluorescent pseudomonads, controls primary and energy metabolism and the expression of virulence (secretion systems) or biocontrol factors, including exoenzymes and secondary metabolites (siderophores, antibiotics, BVOCs) [187][188][189].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported that the production of certain mVOCs can be induced or suppressed during inter-specific microbial interactions (Garbeva et al 2014a;Tyc et al 2015;Piechulla et al 2017).mVOCs were often considered to be by-products of primary metabolism, but recent findings revealed that many mVOCs demonstrate biological activity (Schmidt et al 2015;Tyc et al 2017a). Furthermore, in bacteria, the production of certain mVOCs is dependent on the GacS/GacA two-component regulatory system (Cheng et al 2016;Ossowicki et al 2017). These findings clearly disagree with the opinion that mVOCs are just waste products.…”
Section: Introductionmentioning
confidence: 94%
“…However, VOCs are not simply metabolic 'waste products' which is indicated by their diverse biological activities (Effmert et al 2012;Schmidt et al 2015;. Furthermore, studies revealed that for bacteria the production of certain VOCs with antifungal activity including dimethyl sulfide is regulated by GacS/GacA twocomponent regulatory system or by quorum sensing (Han et al 2006;Müller et al 2009;Cheng et al 2016;Ossowicki et al 2017).…”
Section: Chapter 1 15mentioning
confidence: 99%